Game changers for teacher education - Gibson, David; Knezek, G. (AACE, 2011)
This article introduces ideas for a new framework for teacher education based on two sets of forces that are radically transforming the way educational researchers and practitioners see their world: 1. Complex Systems Knowledge, and 2. Global Flatteners. Complex systems knowledge is part of a new approach in science, a transformation in thinking now maturing towards dynamical systems and evolutionary computational modeling. The global flatteners represent economic game changers brought about by the Internet and the changed business practices it allows. These ideas are game changers for teacher education, preparation and continuing support.